2018
DOI: 10.1117/1.oe.57.8.085101
|View full text |Cite
|
Sign up to set email alerts
|

High-speed three-dimensional shape measurement using phase measurement profilometry without phase unwrapping

Abstract: In the fast three-dimensional (3-D) shape measurement, it is an important factor to use the least number of the fringe pattern to get 3-D shape measurement of arbitrary objects. Although one-shot technologies can use one-frame deformed fringe pattern to get the wrapped phase, they are easily affected by the surface property and suffer from poor spatial resolution. In addition to the process, phase unwrapping may affect the quality of absolute phase. This paper proposes a fast measurement method based on a phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…By comparing data from Table.3, it can be found that the proposed method has the least errors which means the proposed method can acquire the best result compared with other methods. (2) Shiny objects measurement In our previous research [27], phase shifting profilometry with wrapped phase matching (PSP+WP) is proposed. However the measurement result of shiny object is easily affected.…”
Section: B Three-dimensional Measurement Of Complex Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing data from Table.3, it can be found that the proposed method has the least errors which means the proposed method can acquire the best result compared with other methods. (2) Shiny objects measurement In our previous research [27], phase shifting profilometry with wrapped phase matching (PSP+WP) is proposed. However the measurement result of shiny object is easily affected.…”
Section: B Three-dimensional Measurement Of Complex Objectsmentioning
confidence: 99%
“…In practice, the process of phase unwrapping will also increase measurement time. In our previous reference [27], we research the high-speed 3D shape measurement using wrapped phase. However, complex objects will affect the intensity of deformed fringe patterns and the accuracy of wrapped phase will be reduced, especially for discontiuous objects and shiny objects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the signal-to-noise ratio is low when measuring steep surfaces, and there are large shadowed areas, which cannot meet the measurement requirements of industrial scenes. Lu et al 17 also proposed a method based on phase shifting profilometry and stereo vision measurement systems. They used constraints from matched raw images to obtain a rough disparity and used subpixel disparity optimization to reduce matching errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the signal-to-noise ratio is low when measuring steep surfaces, and there are large shadowed areas, which cannot meet the measurement requirements of industrial scenes. Lu et al 17 . also proposed a method based on phase shifting profilometry and stereo vision measurement systems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, three-dimensional (3D) measurement technologies have been studied in detail. Among these technologies, structured light 3D measurement technology has several advantages, such as non-contact, high resolution, high precision, and simple hardware structure [1,2]; thus, it is widely used in quality inspection, reverse engineering, biomedicine, cultural relic protection, and other fields [3][4][5][6]. The monocular structured light 3D measurement system usually comprises a projector, a camera, and a computer; a schematic of the system structure is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%